A deciduous directing group approach for the addition of aryl and vinyl nucleophiles to maleimides. Issue 46 (25th May 2017) - Bettadapur, Kiran R.; Lanke, Veeranjaneyulu; Prabhu, Kandikere Ramaiah
Abstract : A Rh(iii )-catalyzed C–H activation followed by conjugate addition to maleimides, using carboxylic acid as a traceless/deciduous directing group, to formally furnish a Csp 2 –Csp 3 bond is presented. Abstract : A Rh(iii )-catalyzed C–H activation followed by conjugate addition to maleimides, using carboxylic acid as a traceless/deciduous directing group, to formally furnish a Csp 2 –Csp 3 bond is presented. For the first time, derivatives of acrylic acid have been shown as surrogates for the unstable and expensive alkenyl boronic acids.